2017
DOI: 10.1007/s11657-017-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of osteoporosis among female head of household: an Iranian experience

Abstract: Considering the poor awareness level of the studied women and their poor practice of bone healthy behavior, one could conclude that more programs are needed or the content/delivery style of the existing ones should be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Vitamin D fortification varies widely between countries, as detailed in the section on Food fortification with vitamin D. These drawbacks may explain the wide variability between countries and the lack of a consistent pattern by age. The mean vitamin D intake ranged between 1 and 4 µg/ day, with some exceptions in selected groups of children, adolescents and pregnant women, probably due to vitamin D supplements (126,164,165,166,167,168,169,170,171,172,173,174,175,176). These intakes are well below the RDA of 10-20 µg/day, depending on age and reproductive stage (2,177).…”
Section: Vitamin D Intake In the Middle Eastmentioning
confidence: 99%
“…Vitamin D fortification varies widely between countries, as detailed in the section on Food fortification with vitamin D. These drawbacks may explain the wide variability between countries and the lack of a consistent pattern by age. The mean vitamin D intake ranged between 1 and 4 µg/ day, with some exceptions in selected groups of children, adolescents and pregnant women, probably due to vitamin D supplements (126,164,165,166,167,168,169,170,171,172,173,174,175,176). These intakes are well below the RDA of 10-20 µg/day, depending on age and reproductive stage (2,177).…”
Section: Vitamin D Intake In the Middle Eastmentioning
confidence: 99%
“…In another study, Khashayar, P. et al found the awareness of OP only 18.7% among housewives in Iran [12]. Similarly Gopinathan, N. R. and colleagues found that OP awareness was low among postmenopausal women in India [13].…”
Section: Resultsmentioning
confidence: 99%
“…Data were expressed as mean, standard deviation, minimum-maximum and percent (%); where appropriate. [11][12][13][14]. Njeze Ngozi, R. and et al reported the rate of consciousness of OP is 37.4% in southeast Nigeria [11].…”
Section: Discussionmentioning
confidence: 99%
“…There were significant associations between the level of awareness and age, sex, education level, occupation, and income [122]. In contrast, considerable middle aged and elderly Saudi women were unaware of OP risk factors [123]. In Turkish people aged between 40 and 89 years, 19.2% of them had never heard about 'osteoporosis,' and 74% could not describe it.…”
Section: Knowledge and Practices Related To Osteoporosis In Menamentioning
confidence: 96%
“…Of those who knew OP, equal percentages had heard of it from a physician, friend, and from the media [15]. The majority (81%) of Iranian females had a poor knowledge of OP and its complications [123]. Regarding the degree of awareness about various risk factors of OP, only 12% of postmenopausal Palestinian women correctly answered 70% of the knowledge questions about OP (26).…”
Section: Knowledge and Practices Related To Osteoporosis In Menamentioning
confidence: 99%